Teaching Idioms and Phrasal Verbs Creatively (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is dedicated to exploring creative methods for teaching idioms and phrasal verbs in the English lessons. These linguistic units are essential components of authentic communication but they often present difficulties for learners due to their figurative meanings and irregular structure. Theoretically the article outlines the definitions and key characteristics of idioms and phrasal verbs, highlights the main differences between them and explains why these expressions are difficult for students to remember and use. Additionally, it analyzes an overview of commonly used conventional teaching approaches in language structure. Practically the article includes a collection of interactive classroom activities such as role plays, games, visual aids, and personalized tasks designed to help students learn and apply idiomatic expressions in context.